Bimbingan Agama dalam Meretas Buta Huruf Hija’iyah Di MTPQ Baitul Izza Kelurahan Panjang Baru - Rosyad , Muhammad Faiz Ulu; Azzahrina , Khusna; Kibtiyah , Maryatul; Basyar , Khoirul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research endeavours to enhance the ability to read and comprehend the Qur'an among the elderly in Panjang Baru Village, Pekalongan City, grappling with low socio-economic conditions. The initiative is an educational endeavour and a profound commitment to uplift a marginalized demographic's spiritual and intellectual well-being. The program is meticulously designed, focusing on the foundational aspects of learning Iqra 'and Ta'lim Al-Qur'an, essential for overcoming Hijaiyah illiteracy—a barrier often preventing individuals from engaging deeply with their faith. The implementation method is structured into several stages: tahsin, which emphasizes the correct pronunciation and articulation of Arabic letters; reading fluency, which encourages participants to read with confidence and ease; and extracting the meaning of the verses, which fosters a deeper understanding of the Qur'an's teachings. This multi-faceted approach is educational and transformative, as it employs an interactive methodology that promotes active participation and engagement. By orienting the program towards Islamic character development, participants are encouraged to internalize the values of compassion, patience, and community, which are essential traits in Islamic teachings. The evaluation results of this initiative reveal a significant improvement in participants' ability to read the Qur'an accurately and with proper tajweed rules. Furthermore, there is a marked enhancement in their understanding of religious values, which permeates their daily lives. This research underscores the importance of religious education for the elderly, highlighting its potential to enrich their worship experience and cultivate a robust Islamic character within the community. In conclusion, this initiative addresses the immediate educational needs of older people and contributes to the broader goal of fostering a spiritually enriched and socially cohesive society.